License to bully: rites of passage in higher education - da Silva, A. C.; Farhangmehr, M.; Jalali, M. S. (International Review on Public and Nonprofit Marketing, 2018)
This study examines the existence of bullying behaviours in the relatively under-studied setting of higher education institutions (HEI), and in the context of the initiation rites which in many countries come associated with entry into these institutions, in particular. Findings from our in-depth interviews with former, current and prospective university students indicate that bullying in universities exists, is closely intertwined with initiation rituals and their associated activities, and furthermore assumes various forms. This reality leads to a dissonance in respondents’ understanding and descriptions of the initiation rites – a conflict between the intended purpose of integration on the one hand, and the often oppressive practice of these rituals on the other. The initiation rites were furthermore perceived as legitimising and perpetuating otherwise unacceptable and overbearing behaviours. The findings indicate an important role for social marketing in helping mitigate bullying behaviours in initiation rituals, as well as creating upstream pressure for change by policy makers.